Development of BET inhibitors as potential treatments for cancer: A new carboline chemotype. (1st November 2021) - Hill, Matthew D.; Quesnelle, Claude; Tokarski, John; Fang, Haiquan; Fanslau, Carolynn; Haarhoff, Zuzana; Kramer, Melissa; Madari, Shilpa; Wiebesiek, Amy; Morrison, John; Simmermacher-Mayer, Jean; Sinz, Michael; et al.
Graphical abstract: Abstract: We describe our efforts to introduce structural diversity to a previously described triazole-containing N1-carboline series of bromodomain and extra-terminal (BET) inhibitors. N9 carbolines were designed to retain favorable binding interactions that the N1-carbolines possess. A convergent synthetic route enabled modifications to reduce clearance, enhance physicochemical properties, and improve the overall in vitro profile. This work led to the identification of a potent BET inhibitor, ( S )-2‐{8‐fluoro‐5‐[(3‐fluoropyridin‐2‐yl)(oxan‐4‐yl)methyl]‐7‐[4‐( 2 H3 )methyl‐1‐methyl‐1 H ‐1, 2, 3‐triazol‐5‐yl]‐5 H ‐pyrido[3, 2‐b]indol‐3‐yl}propan‐2‐ol (10 ), a compound with enhanced oral exposure in mice. Subsequent evaluation in a mouse triple-negative breast cancer tumor model revealed efficacy at 4 mg/kg of N9-carboline 10 .